2022
DOI: 10.21657/soilst.1218439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N fertilizing on gas exchange, leaf photosynthetic performance and nutrient concentrations of Sweet Cherry cv. 0900 ziraat

Abstract: In this study, the effect of nitrogen (N) fertilization on gas exchange and the photosynthetic performance of cherry leaves were investigated. In the study, 4 different doses of N were applied from the soil, and N, P, K, Ca, Mg, Fe, Mn, Zn, and B concentrations were determined in leaf samples taken from the middle part of the shoots 65-70 days after full flowering. Assimilation rate (A), the concentration of intercellular CO2 (Ci), transpiration rate (Tr), stomatal conductance to water vapor (Gsw), total condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…N application rates and sources promoted diverse effects on gas exchange parameters [29,30]. The application of rates exceeding 110 and 91 kg N ha −1 for stomatal conductance and net photosynthetic rate, respectively, coupled with lower yields, indicates that an increase in N supply beyond the optimal rate disrupts physiological mechanisms, manifesting in diminished tuber biomass production.…”
Section: Discussionmentioning
confidence: 99%
“…N application rates and sources promoted diverse effects on gas exchange parameters [29,30]. The application of rates exceeding 110 and 91 kg N ha −1 for stomatal conductance and net photosynthetic rate, respectively, coupled with lower yields, indicates that an increase in N supply beyond the optimal rate disrupts physiological mechanisms, manifesting in diminished tuber biomass production.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis revealed that 154 key metabolites (VIP >1) could distinguish M1, M2 and M3; 75 metabolites showed an increasing trend in content with an increase of Mg concentration (M1-M3), and the top 4 categories with the highest amount were saccharides (37.33%), nucleotides and derivatives (12.00%), organic acids (9.33%), and amino acids and derivatives (6.67%) (Figure 4A); whereas 79 of 154 key metabolites showed a decreasing trend in content, and the top 4 categories with the highest number were phenolic acids (26.58%), free fatty acids (11.39%), alkaloids (10.13%), and organic acids (10.13%) (Figure 4B). Mg is an important component of plant chlorophyll and pigment, which can promote plant photosynthesis and improve the synthesis of carbohydrate and amino acids (Huang et al, 2021;Ucģun et al, 2022). At the same time, Mg is beneficial to promote plant metabolism, improve plant cell division ability and promote plant growth (Pacheco et al, 2020).…”
Section: Screening Of Key Metabolites In Tea Leaves Under Magnesium R...mentioning
confidence: 99%
“…Saccharides have been reported to be the main product of photosynthesis in plants, and an increase in saccharides content was beneficial to the enhancement of plant metabolism, which in turn increased plant growth rate, while nucleotides and derivatives could promote plant cell division and reproduction (Pacheco et al, 2020;Ucģun et al, 2022). Vitamins help protect plants from the harmful side effects of photosynthesis (S ̌ola et al, 2021).…”
Section: Screening Of Characteristic Metabolites From Key Metabolites...mentioning
confidence: 99%